690 Orthopaedic Trauma Surgery: Has the COVID Pandemic Affected Surgical Outcomes?. (12th October 2021) - Edwards, T; Hristova, K; Shiels, S; Frostick, R; Lostis, E; Kumar, N
Abstract: Aim: To compare the surgical outcomes following orthopaedic trauma surgery before and during the COVID pandemic in an adult Major Trauma Centre. Method: A retrospective chart review was conducted for all patients undergoing orthopaedic trauma surgery before (01/12/2019 to 29/02/2020) and during (01/03/2020 to 10/06/2020) the COVID pandemic. A Chi-square test was used to compare frequencies of type of anaesthetic used, postoperative ITU admission, any surgical complications and mortality. Data was collected 90 days after surgery. Results: During the pre-COVID period, 501 patients (mean age at surgery 64y 4m; 222 male (44%)) underwent orthopaedic trauma surgery (395 lower limb (79%); 86 upper limb (17%); 28 pelvis (6%)) compared to 474 patients (mean age at surgery 61y 8m; 219 male (48%)) during the COVID period (388 lower limb (82%); 58 upper limb (12%); 23 pelvis (5%)). There was a significant increase in the use of a spinal as the main anaesthetic during the pandemic (9 (2%) vs 115 (24%), p < 0.001) and fewer trauma patients were admitted to ITU postoperatively (42 (8%) vs 16 (3%), p0.001). There was no difference in the rate of postoperative complications (103 (21%) vs 95 (20%), p0.841) or mortality at 90 days (42 (8%) vs 43 (9%), p0.703). Of the 244 COVID swabs done during the COVID period, 8 (3%) were positive. Conclusions: Despite widespread operational disruption and a change in anaesthetic practice, there was no change in the rate of postoperative complications or mortality following orthopaedic trauma surgery.